The role of media socialization agents in increasing obesity health literacy among Malaysian youth - Eng, May Chuen; Michael, Edwin; Teh, Boon Teck (Penerbit Universiti Kebangsaan Malaysia, 2016)
Obesity is a global emerging issue. In Malaysia, there has been a significant increase in such cases in the past few years. It is a big challenge for authorities to find out the effectiveness of newspaper as a medium for disseminating obesity information among Malaysian youth. This study aimed to examine the influences and effectiveness of newspaper in conveying health literacy of obesity among Malaysian youth. It focused on their awareness level and perception towards obesity. In this study, 300 Malaysian youth aged 18-25 participated in a survey. It was found that the newspaper-oriented respondents have higher awareness of obesity than the non-newspaper oriented respondents. However, the awareness among the overall respondents is still mainly average. The results also indicate that newspaper is still resourceful in disseminating health information. It is significantly positively related to the youth health literacy.